STRATEGI PEMBELAJARAN BAHASA INDONESIA YANG EFEKTIF: TINJAUAN LITERATUR - Neura Shafa Salsabila; Laura Apriyola Atmaja; Helty; Liza Septa Wilyantis (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study is a literature review aimed at identifying, analyzing, and comparing various Indonesian language learning strategies that are considered effective based on scientific literature published between 2020 and 2026. The main issue underlying this study is the relatively low quality of Indonesian language learning at various educational levels, which is partly caused by the mismatch between teaching strategies and students’ learning characteristics and needs. Through the analysis of 25 scientific sources, including journal articles, research reports, and international conference proceedings, this study examines six major strategies: Cooperative Learning, Project-Based Learning (PjBL), Discovery Learning, Contextual Teaching and Learning (CTL), Differentiated Instruction, and Literacy – Based Learning Strategies. The findings indicate that these strategies consistently contribute to increasing students’ active engagement, strengthening language proficiency, and promoting critical thinking skills. No single strategy is universally superior in all situations; the effectiveness of a strategy largely depends on learning objectives, student characteristics, and classroom conditions. This study concludes that the most effective learning approach is one that is student – centered, contextual, and adaptive to diverse learning needs. The practical implication for educators is the need for flexibility in selecting and combining learning strategies according to the specific context they encounter.